WAIS Divide Core 10Be data, 2850-3240 m ... - Caffee, Marc W.; Welten, Kees; Woodruff, Thomas E (U.S. Antarctic Program (USAP) Data Center, 2023)
This dataset contains a continuous depth profile of 10Be measured in ice core samples from the WAIS Divide Core between 2850 and 3240 m depth. ...